THE GENERAL THEORY OF STATE AND LAW IN THE SYSTEM OF LEGAL SCIENCES (ANALYSIS OF S. S. ALEKSEEV’S CONCEPT) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
During the period of methodological pluralism, researchers and other persons had the opportunity to study legal phenomena from different sides, based on different concepts and approaches, which are often justified by polar opposite arguments. This situation also affects the educational literature. Meanwhile, it is necessary to analyze the basic concepts of a methodological nature, which will allow maintaining the level of scientific research in the state-legal reality and the continuity of the tradition of domestic jurisprudence. The creative legacy of S. S. Alekseev can be a reliable guide in this activity.
Keywords: jurisprudence; legal science; law; general theory of state and law; theory of state and law